2014
DOI: 10.1007/s10753-014-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Therapeutic Effect of Apocynin on Bleomycin-Induced Lung Fibrosis in Rats

Abstract: We aimed to investigate the preventive and therapeutic effect of apocynin (APO) on bleomycin (BLC)-induced lung injury in rats. Rats were assigned into groups as follows: control group; APO group, 20 mg/kg APO was given intraperitoneal for 29 days; BLC-1 and BLC-2 groups, a single intratracheal injection of BLC (2.5 mg/kg); APO+BLC-preventive group, 20 mg/kg APO was administered 12 h before the intratracheal BLC injection and continued for 14 days; BLC+APO-treatment group, 20 mg/kg APO was given on the 14th da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
4
17
0
2
Order By: Relevance
“…However, MDA is a kind of aldehyde produced through the lipid peroxidation process, which can promote crosslinking of nucleic acids, proteins, and phospholipids and change the function of these biological macromolecules. The level of lipid peroxidation can be represented by MDA content [49, 50]. Conversely, SOD can transform superoxide anions into H 2 O 2 , thereby eliminating superoxide anions and protecting cells from oxygen radical injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, MDA is a kind of aldehyde produced through the lipid peroxidation process, which can promote crosslinking of nucleic acids, proteins, and phospholipids and change the function of these biological macromolecules. The level of lipid peroxidation can be represented by MDA content [49, 50]. Conversely, SOD can transform superoxide anions into H 2 O 2 , thereby eliminating superoxide anions and protecting cells from oxygen radical injury.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase inhibitor apocynin significantly inhibited the OTA-induced mesangial cytotoxicity and apoptosis. Several studies have demonstrated that apocynin has therapeutic effect on multiple animal disease model including chemically-induced colitis in mice [28], testicular ischemia-reperfusion injury in rats [29], bleomycin-induced lung fibrosis in rats [30], Cyclosporine A-Induced hypertension and nephrotoxicity in rats [31], established alcoholic steatohepatitis rat model [32], and contrast-induced nephropathy in the diabetic rats [33]. Therefore, these findings indicate that the concentrations of OTA used in this cellular toxicological study are reasonable and effectively induce mesangial cell cytotoxicity via a NADPH oxidase-derived ROS-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were routinely passaged by trypsinization after they reached 80% confluence using 10-cm culture dishes and incubating them at 37°C in a humidified chamber with a 5% CO 2 /95% air mixture. RMCs were obtained by culturing glomeruli isolated from kidneys of 100- to 150-g male Sprague-Dawley rats by conventional sieving methods as described previously [30]. Cells were cultured in DMEM containing 20% fetal bovine serum (FBS), 100 U/ml penicillin, 100 μg/ml streptomycin, 44 mM NaHCO 3 , and 14 mM HEPES.…”
Section: Methodsmentioning
confidence: 99%
“…Grup: Santral 5 mm ön kapsülün künt spatül ile polisaj yapılarak katarakt (perforasyonsuz) oluşturulup 21 gün boyunca intraperitoneal 2 mL fosfat tamponlu salin içinde 20 mg/kg/gün aposinin (Apocynin, Sigma-Aldrich, ABD) verilen grup idi. 12 Hayvanlara günlük olarak biyomikroskobik muayene yapıldı. Göz içi basınçları perkins tonometre (Haag-Streit, Birleşik Krallık) ile öl-çüldü.…”
Section: Gereç Ve Yöntemlerunclassified
“…9 Aposinin, birçok alanda çalışmalarda kullanılmış ve çeşitli nedenlerden kaynaklanan oksidatif hasarların azaltılmasında etkili bulunmuştur. [10][11][12][13][14] Bu çalışmada, yeni bir travmatik katarakt modeli oluşturarak, aposinin molekülünün travmatik katarakt üzerine olan etkisinin incelenmesi amaç-lanmıştır.…”
unclassified